2015
DOI: 10.1038/ismej.2015.118
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of timber harvesting on hemicellulolytic microbial populations in coniferous forest soils

Abstract: Forest ecosystems need to be sustainably managed, as they are major reservoirs of biodiversity, provide important economic resources and modulate global climate. We have a poor knowledge of populations responsible for key biomass degradation processes in forest soils and the effects of forest harvesting on these populations. Here, we investigated the effects of three timber-harvesting methods, varying in the degree of organic matter removal, on putatively hemicellulolytic bacterial and fungal populations 10 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 67 publications
4
32
0
Order By: Relevance
“…In our study, fungal community showed lower α‐diversity (Supplemental Table ) and fewer specific fungal OTUs were identified compared with bacterial community (Table ). Consistent with previous studies using SIP method (Leung et al., ; Stursová, Zifčáková, Leigh, Burgess, & Baldrian, ), Ascomycota also accounted for the majority of total community in 13 C‐heavy fraction (Figure 5b). The genera Chaetomium , Mortierella and Curvularia , which are known to be involved in hemicellulose degradation (Zeng et al., ), were the initial fungal groups assimilating straw‐derived 13 C at Day 3.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, fungal community showed lower α‐diversity (Supplemental Table ) and fewer specific fungal OTUs were identified compared with bacterial community (Table ). Consistent with previous studies using SIP method (Leung et al., ; Stursová, Zifčáková, Leigh, Burgess, & Baldrian, ), Ascomycota also accounted for the majority of total community in 13 C‐heavy fraction (Figure 5b). The genera Chaetomium , Mortierella and Curvularia , which are known to be involved in hemicellulose degradation (Zeng et al., ), were the initial fungal groups assimilating straw‐derived 13 C at Day 3.…”
Section: Discussionsupporting
confidence: 90%
“…Generally, bacteria degrade labile organic matter more actively in the early phase of straw decomposition, while fungi are responsible for the degradation of complex and recalcitrant substrates at later stages (Paterson et al., ). For instance, members of the genera Bacillus and Paenibacillus have been identified as decomposers of labile C (Verastegui et al., ), while members of the phylum Ascomycota have strong cellulolytic and hemicellulolytic capabilities (Leung, Maas, Wilhelm, & Mohn, ). Recently, it was also suggested that, like fungi, bacteria potentially play a significant role in the mineralization of recalcitrant components (Bastian, Bouziri, Nicolardot, & Ranjard, ; España et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Soil is the major sink for COS from the atmosphere, and rotary tillage would expose to the soil to more COS than no tillage or deep tillage treatments. It is well known that Methylibium possess the ability to degrade hemicellulose, which is abundant in crop straw (Leung et al ). Although few studies have investigated the relationship between Methylibium and tillage practices, it is known to be a monoaromatic hydrocarbon degrading bacterium (Salvador et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Microcosms were wetted and pre-incubated in the dark at 20° C for one-week prior to the addition of 1% (w/w) 13 C-labeled cellulose or 0.8% (w/w) lignin. The hemicellulose-amended incubations were performed as part of a previous study examining the impacts of timber harvesting on decomposition using identical methods as described here for cellulose (Leung et al , 2016). Each microcosm with 13 C-labeled substrate was paired with an identical ‘ 12 C-control’ microcosm amended with the corresponding unlabeled substrate (~1.1% atom 13 C).…”
Section: Methodsmentioning
confidence: 99%
“…Microcosms were incubated at 20° C for 14 days (cellulose) or 60 days (lignin) or 2 days (hemicellulose; Leung et al , 2016). The incubation length for this study was optimized by preliminary time-course experiments described in Wilhelm et al (2014).…”
Section: Methodsmentioning
confidence: 99%